Postpoziciniai vietininkai J. Bretkūno „Evangelijos pagal Luką“ vertime - Gelumbeckaitė, Jolanta (Baltistica, 1997)
THE POSTPOSITIONAL LOCATIVES IN THE TRANSLATION OF THE GOSPEL ACCORDING TO LUKE BY J. BRETKŪNAS The article deals with a syntactic and semantic system of 4 Old Lithuanian locatives (PLs) in J. Bretkūnas’ Gospel according to Luke. A particular feature of Luke is that it was translated from Latin, while the rest of the NT was translated from different German editions of M. Luther’s Bible. There have been some attempts to identify the edition of the Vulgate which J. Bretkūnas chose for the translation of Luke, but this problem is not entirely solved. A more detailed analysis and comparison of Luke with some 16th c. editions of the NT allowed me to draw a preliminary conclusion that J. Bretkūnas used (beside the Versio Erasmi) the Editio Wittembergae of 1529. In all likelihood he also used the Editio Cōplutensae (the Complutensian Polyglot Bible) of 1521. In the 16th c. Lithuanian the postpositional case forms were used in certain meanings in the contexts where prepositional phrases (PPs) predominate nowadays. 26,2% of Latin PPs correspond to the Iness., Ill., Adess. or All. The PLs are distinct in their syntactic and semantic functions while case syncretism in Latin has caused more explicit express of overlapped semantic value of some cases in a sentence. In order to establish semantic boundaries of the PLs it was reasonable to specify the functions of spatio-temporal location or direction more precisely. Thus the following semantic functions are distinguished: 1) place within (it also includes the aspects of a) inner state, and b) process(es) in mind), 2) place at/near, 3) place/spread within/ among, 4) movement into, 5) movement toward (which figuratively is related with the function of), 6) addressee, and 7) determined interval of time. In many cases the PPs stimulated usage of the autochtonous Lithuanian means. Although there are instances of an obvious interference of Latin with the continuation of such patterns observed in Modern Lithuanian. A puzzling case appears at a semantic level – the Adess. does not happen to bear its main function (place at/near), more often it denotes process(es) in mind.